Informe No 136/99. Caso 10.488. Ignacio Ellacuría, S.J.; Segundo Montes, S.J.; Armando López, S.J.; Ignacio Martín Baró, S.J.; Joaquín López y López, S.J.; Juan Ramón Moreno, S.J.; Julia Elba Ramos; y Celina Mariceth Ramos. El Salvador. 22 de diciembre de 1999 - Editor, El (ECA: Estudios Centroamericanos, 2000)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 55, No. 615-616, 2000: 143-183.